An Article Review: Charge-Transfer of Polyenes and Carotenes - Azhar Mohammed Hasan Wahhab; Hamsa M. Yaseen (Ibn Al-Haitham Journal for Pure and Applied Sciences)
When an electron moves from one atom or molecule to another, a charge-transfer complex is formed. The other objects must be able to accept these electrons, and one entity must have free electrons or a tendency to donate them. This resembles an internal oxidation-reduction reaction more. This research aims to shed light on charge transfer complexes formed by polyenes and carotenes, which act as electron-donating molecules due to their alternating double and single bonds. This allows them to create such complexes when interacting with organic molecules that lack electrons. These complexes exhibited distinctive optical and physicochemical properties, enabling them to be adapted for a wide range of applications. In addition, the researchers demonstrated significant interest in the study of the ability of some of these compounds to form self-internal charge-transfer complexes, also known as intramolecular charge-transfer complexes, and their precise electronic and dynamic states.